Pengaruh desain sampul buku terhadap minat baca pada ruang koleksi anak di Dinas Perpustakaan dan Kearsipan Kabupaten Tanjung Jabung Timur: Desain Cover Buku, Minat Baca, Ruang Koleksi Anak - Ariska Idamayanti; Sri Rohyanti Zulaikha; Rory Ramayanti; Fridinanti Yusufhin (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2024)
Librarians, both adults and children, have the freedom to determine what collection they want when they are in the library, however, in choosing a collection of library materials, children generally look for collections that have a variety of pictures because according to the children The collection is equipped with various kinds of images which have their own uniqueness. This research aims to:to prove and find out the extent of the influence of book cover design on reading interest in children's collection rooms. This research uses quantitative methods with a correlational research type. Data collection was carried out through observation and distributing questionnaires to 256 children who were members of the children's collection room. The results of the research on the normality test show that there is a relationship between book cover design and children's reading interest in the DPK, East Tanjung Jabung Regency, with the value Pearson Chi-Square on Asymp. Say. (2-sided) is 0.007 < 0.05, so Ho is rejected and Ha is accepted. In the linearity test, it was found that the relationship was linear because the significance value was greater than the significance level, namely 0.499, where 0.499 > 0.05. Hypothesis testing shows that there is a significant influence between book cover design and children's reading interest, with a value of > , namely 9.888 > 1.650. That the influence of book cover design on reading interest is 27.8%, while the remaining 72.2% is influenced by other factors.